Unravelling the Economic Impacts: Forecasting the Effects of the February Earthquakes on Türkiye’s Economy - Ismail Demirdag; Anang Widhi Nirwansyah (Journal of Regional and City Planning, 2024)
This study aimed to reveal the macroeconomic effects of the earthquakes that occurred in Türkiye in February 2023 on the country as a whole, the affected region (covering 11 provinces), and other provinces. Using secondary data obtained from data sets of various institutions, this research firstly attempted to estimate the negative effects of the February Earthquakes on the country’s GDP. The study presents a base scenario using the economic growth forecasts of international organizations such as the IMF and the World Bank for 2023 and 2024 as well as three possible loss scenarios for Türkiye, taking into account the effects of earthquakes of similar magnitude on the GDP in Türkiye and other countries. Furthermore, this study tried to estimate the losses caused by earthquakes in terms of employment, GDP, agriculture, industry, services, and foreign trade at the regional and provincial levels. To do this, we created the Base Scenario, which assumes no earthquake, and Scenario 1, which shows the impact of the earthquake. The findings indicate that, in the worst-case scenario, the country will contract by approximately 2.75%, which means a loss of $8.8 billion. Moreover, the study results point out an average monthly loss of 242 thousand jobs, a loss of $5 billion in GDP, an export loss of $3.5 billion, and an import loss of $4.7 billion in the 11 earthquake-affected provinces. The research underlines the need for comprehensive measures to mitigate the economic consequences caused by earthquakes. This includes disaster prevention plans, effective management strategies and initiatives aimed at strengthening regional economic resilience. Ultimately, the article provides valuable information for policymakers to facilitate informed decisions and the implementation of measures to increase preparedness, risk mitigation, and sustainable recovery in earthquake-prone areas.